Case Report: Transferable IncX4 plasmid carrying mcr-1 in colistin-resistant Escherichia coli from a healthy pet dog in South Korea - Oh, Jae Young; Kwak, Su Min; Kim, Joo Yeol; Ro, Woong-Bin; Lee, Kwang Jun; Chae, Jong-Chan (Frontiers in Veterinary Science, 2026)
Colistin resistance mediated by the plasmid-borne mcr-1 gene presents a significant challenge in both human and veterinary medicine. While colistin-resistant bacteria have been reported in food-producing animals and humans, mcr-1-harboring strains remain relatively underreported in companion animals, particularly in South Korea. In this study, a colistin-resistant Escherichia coli strain Z1324PEC0026 was isolated from a clinically healthy companion dog owned by a veterinary nurse, which exhibited resistance to multiple antimicrobials, including colistin, β-lactams, aminoglycosides, tetracyclines, and phenicols. Its genome harbored two plasmids: a 33.9 kb IncX4 plasmid pEC027-3 carrying mcr-1 gene with a high conjugation frequency, 4.64 × 10−2 per recipient cell, and another plasmid pEC027-2 carrying additional resistance genes such as blaCTX-M-55, blaOXA-10, qnrS1, dfrA14, aph(3”)-Ia, aadA1, cmlA1, arr-2, and tet(A). The genetic structure of pEC027-3 exhibited high synteny with global IncX4 plasmids but showed divergence from mcr-1-carrying plasmids previously reported in South Korea, suggesting an independent origin. The presence of a transferable mcr-1-harboring IncX4 plasmid in a healthy dog with no prior colistin exposure implies the risk of silent dissemination of antimicrobial resistance.